2016
DOI: 10.1504/ijasm.2016.078575
|View full text |Cite
|
Sign up to set email alerts
|

Managing conflict in organisational change

Abstract: Organisational change and conflict are two essential topics that engineering managers need to understand and have confidence in acting on, if they are to succeed in today's changing and increasingly competitive environment. This paper examines and dissects the elements of organisational change that almost inevitably result in conflict. Conflicts that impact on organisational change can act as a retardant to progress, creativity, innovation and productivity, and potentially precipitate the demise of an organisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Effective conflict management is a hallmark of good leadership. Because conflict management is quickly becoming a critical and time-consuming aspect of management, managers must be prepared to face these challenges and handle conflicts in the organization into constructive results (Kiitam, McLay, & Pili, 2016). Leaders can make conflict as a means to make the learning process sustainable and trigger productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Effective conflict management is a hallmark of good leadership. Because conflict management is quickly becoming a critical and time-consuming aspect of management, managers must be prepared to face these challenges and handle conflicts in the organization into constructive results (Kiitam, McLay, & Pili, 2016). Leaders can make conflict as a means to make the learning process sustainable and trigger productivity.…”
Section: Resultsmentioning
confidence: 99%
“…This occurs when conflict risk has not been effectively mitigated and managed. Various researchers including Chaudhry and Asif (2015) and Kiitam et al (2016) have suggested that conflict risk within development teams most times brings negative outcomes because it yields to several repercussions like the lack of timely communication.…”
Section: Influence Of Conflict As a Risk In Agile Teamsmentioning
confidence: 99%
“…Researchers Crawford et al (2014); Saxena et al (2016) and Gren (2017) have investigated the conflict within Agile environments, its relative sources as well as means of handling and managing it to enable better team collaborations. Effective teams are the ground work for every successful organisation, and organisations generally fail at their strategic goals if they lack effective teams (Kiitam et al 2016). Organisations without teams who work well together normally struggle, even with the simplest task implemented, while effective teams support in improved quality, facilitation of the completion of projects and aid in increasing productivity and efficiency (Anumah 2017).…”
Section: Conceptual Framework For Conflict-risk Managementmentioning
confidence: 99%
See 2 more Smart Citations